Narrative persuasion - Kai Barron; Tilman Fries (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2024)
We study how one person may shape the way another person interprets objective information. They do this by proposing a sense-making explanation (or narrative). Using a theory-driven experiment, we investigate the mechanics of such narrative persuasion. Our results reveal several insights. First, narratives are persuasive: We find that they systematically shift beliefs. Second, narrative fit (coherence with the facts) is a key determinant of persuasiveness. Third, this fit-heuristic is anticipated by narrative-senders, who systematically tailor their narratives to the facts. Fourth, the features of a competing narrative predictably influence both narrative construction and adoption.
Additional information: January 2023 (revised April 2024)
Keywords: D83; G40; G50; C90; 330; Narratives; beliefs; explanations; mental models; experiment; financial advice